Product and process design principles : synthesis, analysis, and evaluation - Seider, Warren D., ....-; Lewin, Daniel R., ....-; Seader, J. D., ....- (New York : Wiley, 2004)
Organization of text follows the key steps in product and process design, reflecting current practices and providing a sound, but flexible, sequence of instruction. Process simulators, steady state, dynamic, and batch, are used throughout the textbook (ASPEN PLUS, HYSYS.Plant, CHEMCAD, PRO/II, BATCH PLUS, and SUPERPRO DESIGNER). Illustrates the design strategies by applying them to chemical products and processes in several industries; for example, the chemicals, petrochemicals, petroleum, polymers, biochemicals, and electronic materials industries. The accompanying CD (now bound into the text) uses voice, video, and animation to introduce students to process stimulators with an emphasis on ASPEN PLUS and HYSYS.Plant. Files containing the solutions to over 60 examples using either ASPEN PLUS or HYSYS. Plant can be used to vary operating strategies and design details. Emphasizes the importance of assessing plant-wide controllability.